Disease threats to the endangered Iberian lynx (Lynx pardinus) - Millán, Javier (Vet J, 2009)
The Iberian lynx, (Lynx pardinus), is the most endangered felid in the world. To determine whether sympatric carnivores are reservoirs of pathogens posing a disease risk for the lynx, evidence of exposure to 17 viral, bacterial and protozoan agents was investigated in 176 carnivores comprising 26 free-living lynx, 53 domestic cats, 28 dogs, 33 red foxes (Vulpes vulpes), 24 Egyptian mongooses (Herpestes ichneumon), 10 common genets (Genetta genetta) and 2 Eurasian badgers (Meles meles) in the areas inhabited by the last two populations of Iberian lynx, both in Andalusia (South-Western Spain). The results indicated that the lynx had low rates of contact with viral pathogens, with one seropositive finding each for feline leukemia virus, parvovirus and canine adenovirus-1, whereas contact with bacteria and protozoa appeared more frequent. Active infections with parvovirus, Ehrlichia spp., Mycobacterium bovis, Leptospira interrogans and Cytauxzoon spp. were confirmed. In contrast, 53% of the domestic cats were exposed to some infectious agent (prevalence range 4.5–11.4%). Antibodies to canine distemper virus and parvovirus were frequently found in dogs (32% and 42%, respectively) and foxes (30% and 12%). Past or present infections with parvovirus, Ehrlichia spp., Chlamydophila spp., M. bovis, Salmonella enterica, L. interrogans, Toxoplasma gondii, and Neospora caninum were also detected in these and other species surveyed. Questionnaires to owners revealed that 14% of the dogs but none of the cats had been vaccinated, and no cat had been neutered. Based on the apparent absence of acquired immunity of the lynx against infectious agents, the frequent detection of agents among sympatric carnivores, and the reported lack of immunocompetence of the Iberian lynx, a disease outbreak among the local abundant carnivores may pose a serious disease risk for lynx conservation.